Liver abscesses in feedlot cattle: impact on meat quality and an alternative to antibiotic use for prevention - McCoy, Elsie Jean (Kansas State University, 2020)
Liver abscesses are both a significant economic loss and animal health and welfare concern for the beef cattle feedlot industry. Currently, in-feed antibiotics are used daily throughout the finishing period to decrease prevalence and severity of liver abscesses seen at the time of slaughter. The use of antibiotics in food animal production has been under scrutiny by consumers and the associated emergence and dissemination of antibiotic resistance is of public health concern. The most common antibiotic used to prevent liver abscesses is tylosin, a macrolide antibiotic. This antibiotic class has been deemed a critically important drug class to human medicine by the FDA, and therefore tylosin is regulated by the Veterinary Feed Directive. The goal of this research was to assess the effect of liver abscesses on meat tenderness and sensory traits and evaluate the safety and efficacy of an autogenous vaccine, an antibiotic alternative, against Fusobacterium necrophorum at reducing liver abscess prevalence and severity in feedlot cattle. The first study assessed the Warner Bratzler Shear Force, Slice Shear Force, and meat sensory panel results for strip loin steaks in a 3 x 2 factorial treatment structure including variables of quality grade: Choice and Select in relation to liver abscess treatment group: normal, mild, and severely abscessed livers. The results of this study showed that liver abscess status had no effect on Warner-Braztler Shear Force or Slice Shear Force but in sensory analysis, quality grade select steaks from cattle with mild liver abscesses were found to have greater myofibril tenderness than those with severe liver abscesses. The second study assessed the safety of an experimental autogenous liver abscess vaccine with three different proprietary adjuvant combinations, adjuvant 1 at 20% concentration, adjuvant 1 at 10% concentration, and adjuvant 2 at 15% concentration in beef cattle. All three antigen-adjuvant combinations were safe and did not elevate body temperature. The final study assessed the efficacy of an autogenous vaccine in a commercial feedlot on cattle enrolled in a “natural” cattle program, therefore raised without antibiotics. This study found that the vaccine did not reduce prevalence or severity of liver abscesses in feedlot cattle that had been fed an average of 206 days. The research outlined in this dissertation adds to the existing body of work about the effects of liver abscesses on carcass quality and outlines the safety and efficacy of an autogenous vaccine developed with the goal of reducing liver abscess prevalence. Liver abscesses in fed cattle must be addressed to improve animal health and welfare and increase profit for producers in an already small margins industry.
Keywords: Beef cattle; Vaccination; Liver abscesses; Feedlot; Meat tenderness